ANALISIS ASESMEN KURIKULUM MERDEKA PADA PEMBELAJARAN IPAS KELAS IV SDN 07 AIR MANIS - Asrizal Ramadhan; Yona Syaida Oktira (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by changes in the assessment system accompanying the implementation of the Kurikulum Merdeka (Independent Curriculum), specifically for the Natural and Social Sciences (IPAS) subject. The primary issues examined include the planning, implementation, challenges, and solutions regarding Kurikulum Merdeka assessments in Grade IV IPAS instruction at SD Negeri 07 Air Manis. The study aims to describe the actual implementation of assessments and the challenges faced by educators. A descriptive qualitative research design was employed, utilizing data collection techniques such as observation, interviews, and document analysis. The research subjects consisted of the school principal and the Grade IV teacher. Data analysis followed the Miles and Huberman model, while data validity was verified through triangulation. The results indicate that during the planning stage, the teacher developed diagnostic, formative, and summative assessment plans incorporated into the Teaching Module and the Learning Objective Flow. During the implementation stage, the assessment process was student-centered, utilizing methods such as question-and-answer sessions, group assignments, and written tests. Challenges faced by the teacher included administrative burdens and time constraints, with solutions involving the simplification of documentation and strengthened collaboration among teachers. It is concluded that assessment implementation at the school has proceeded effectively and in accordance with the Decree of the Minister of Education, Culture, Research, and Technology (Kepmendikbudristek) Number 56 of 2022, despite some shortcomings regarding administrative completeness.